Exchange rate exposure and foreign market volatility: Evidence from Malaysian firms / Nor Azura Razali - Razali, Nor Azura (2007)
This research focuses on the effects of exchange rate to the export and import, evidence from Malaysian firms. This study will examine on how the exchange rate volatility influence the variability of import and export for Malaysia. The objective of this paper is to examine whether there are any significant effects between exchange rate fluctuation to the import and export variability. The method used will be the Single Linear Regression to regress the exchange rate and import and export. The data taken will be on quarterly basis for twelve years period from 1987 until 1998. The time series selected was based on the purpose to skip the period of pegging in ringgit. Based on the method used, this study found that there was a positive correlation between exchange rate and import and the same goes to export. It explained that the devaluation of home currency can benefit the country trade in terms of increasing in Malaysia's export. However, the depreciation in ringgit will not reduce the Malaysia's import. The variability of import and export to be explained by exchange rate is too low but they are significant.